Analisis Kontribusi Pedagang Perempuan Untuk Perekonomian Keluarga Di Pasar Aurduri Kota Jambi - Elyanti Rosmanidar; Agusriandi Agusriandi; Bima Afandy Daulay (STEKOM PRESS, 2024)
This research aims to find out what factors cause more women to sell at the Aurduri market, how women contribute to helping their family's economy, and to find out the obstacles faced by women traders at the Aurduri market. This research uses qualitative methods, with data collection techniques through observation interviews and documentation. The results of the research show that there are three factors that cause women to sell more at the Aurduri market, namely: first, the family economic factor, where the husband's income is insufficient for daily living needs. The second factor is education and age, where female traders who have low education and are quite old and do not have the qualifications to work in other places, because they are old, but they are still fit and productive to work, decide to become traders at the Aurduri market. The three self-actualization factors from the research show that the informants admitted that they enjoyed selling at the market because apart from being able to meet friends, filling in their free time also increased their income. The contribution of female traders to the family is classified as medium to high, which can be seen from the results of their sales which are used for daily needs, to increase family income, and also for savings. There are two obstacles faced by women traders, namely the weather conditions when it falls, secondly, the large number of home-scale vegetable sellers competes with the prices and completeness of goods which are available in almost every neighborhood and housing complex, especially on the road to the Aurduri market.